2017
DOI: 10.1002/admt.201600290
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area, All‐Solid, and Flexible Electric Double Layer Capacitors Based on CNT Fiber Electrodes and Polymer Electrolytes

Abstract: This work presents a scalable method to produce robust all-solid electric double layer capacitors (EDLCs), compatible with roll-to-roll processes and structural laminate composite fabrication. It consists in sandwiching and pressing an ionic liquid (IL) based polymer electrolyte membrane between two CNT fiber sheet electrodes at room temperature, and laminating with ordinary plastic film. This fabrication method is demonstrated by assembling large area devices of up to 100 cm 2 with electrodes fabricated in-ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 57 publications
1
57
0
Order By: Relevance
“…Noting that these capacitive contributions are in series ( 1 = 1 + 1 ), the increase in CQ makes it less accessible, making the electrostatic component of capacitance corresponding to formation of electric-double layer (CEDL) more dominant and hence reducing the dependence of total capacitance on electrochemical potential. Finally, we use functionalized CNTFs to assemble all-solid supercapacitor devices with a polymer electrolyte, following the method described before 62 . Briefly, the process consists of pressing together a sandwich structure of two CNTF electrodes and a membrane of PVDF-HPF and PYR14TFSI, without need for a separator.…”
Section: Resultsmentioning
confidence: 99%
“…Noting that these capacitive contributions are in series ( 1 = 1 + 1 ), the increase in CQ makes it less accessible, making the electrostatic component of capacitance corresponding to formation of electric-double layer (CEDL) more dominant and hence reducing the dependence of total capacitance on electrochemical potential. Finally, we use functionalized CNTFs to assemble all-solid supercapacitor devices with a polymer electrolyte, following the method described before 62 . Briefly, the process consists of pressing together a sandwich structure of two CNTF electrodes and a membrane of PVDF-HPF and PYR14TFSI, without need for a separator.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ah ighly flexible solid-states upercapacitorb ased on ag raphene/polypyrrole hydrogel with long cycle performance was prepared by as imple heating approach. [35] The graphene/polypyrrole hydrogel electrode had superior capacitive performance and excellent cycles tability. The superior performance of the device demonstrated that hybrid hydrogel has ap romising future for applications in wearable supercapacitors.…”
Section: Energystoragementioning
confidence: 99%
“…Therefore, they exhibit elevated capacitance than electrical double‐layer capacitors and better cycling stability than pseudocapacitors. For example, a highly flexible solid‐state supercapacitor based on a graphene/polypyrrole hydrogel with long cycle performance was prepared by a simple heating approach . The graphene/polypyrrole hydrogel electrode had superior capacitive performance and excellent cycle stability.…”
Section: Applications In Flexible Electronic Devicesmentioning
confidence: 99%
See 2 more Smart Citations